Pelaksanaan Pembelajaran Matematika bagi Siswa Tunanetra kelas XI di SMK Negeri 7 Padang pada masa Pandemi Covid-19 - Suzana, Veronica; Sopandi, Asep Ahmad (Universitas Negeri Padang, 2021)
This research was motivated by problems found in one of the schools that provided inclusive education, namely SMK N 7 Padang regarding the implementation of matematics learning for blind students of class XI during the Covid-19 pandemic. This study aims to determine how the implementation of mathematics learning for class XI blind students at SMK N 7 Padang. The method used is descriptive qualitative, the research subjects are mathematics teacher, special guidance teachers, class teachers, blind students(D), parents of blind students. The data collected through observation, interviews, and documentation studies are then analyzed, presented and conclusions drawn from these data. The implementation of mathematics learning for blind students (D) during the pandemic is carried out the same as other regular students using chat applications, where in the application the teacher will condition all teaching and learning activities starting from taking attendance, delivering material in the from of videos, asking and evaluating. Contsraints in implementing mathematics learning for blind students (D) students find it difficult to understand the learning that is given online because online students are accompanied by parents.